Expression and copy number gains of the RET gene in 631 early and mid stage non‐small cell lung cancer cases. Issue 4 (23rd February 2018) - Tan, Ling; Hu, Yerong; Tao, Yongguang; Wang, Bin; Xiao, Jun; Tang, Zhenjie; Lu, Ting; Tang, Hao
Abstract : Background: To identify whether RET is a potential target for NSCLC treatment, we examined the status of the RET gene in 631 early and mid stage NSCLC cases from south central China. Methods: RET expression was identified by Western blot. RET ‐positive expression samples were verified by immunohistochemistry. RET gene mutation, copy number variation, and rearrangement were analyzed by DNA Sanger sequencing, TaqMan copy number assays, and reverse transcription‐PCR. ALK and ROS1 expression levels were tested by Western blot and EGFR mutation using Sanger sequencing. Results: The RET ‐positive rate was 2.5% (16/631). RET ‐positive expression was related to poorer tumor differentiation ( P < 0.05). In the 16 RET‐positive samples, only two samples of moderately and poorly differentiated lung adenocarcinomas displayed RET rearrangement, both in RET ‐ KIF5B fusion partners. Neither ALK nor ROS1 translocation was found. The EGFR mutation rate in RET ‐positive samples was significantly lower than in RET ‐negative samples ( P < 0.05). Conclusion: RET ‐positive expression in early and mid stage NSCLC cases from south central China is relatively low and is related to poorer tumor differentiation. RET gene alterations (copy number gain and rearrangement) exist in all RET ‐positive samples. RET ‐positive expression is a relatively independent factor in NSCLC patients, which indicates that the RET gene may be a novel target site for personalized treatment of NSCLC.